THE RELATIONSHIP BETWEEN MADRASAH AND TEACHER LEARNING STYLE WITH ARABIC LEARNING OUTCOMES - Asmawati Asmawati; Mahyudin Ritonga; Ahmad Lahmi (Linguistik : Jurnal Bahasa dan Sastra, 2021)
The main problem in this study is the madarasah environment, namely the classrooms that do not match the number of students at MTs Negeri 1 Pasaman Barat. It causes the  students undergo the teaching and learning process in the madrasah hall and in the library room, incomplete learning equipment, and the absence of student cooperatives. The monotonous teaching style results  low student achievement, as there are teachers who are still not optimal in providing variations in teaching styles in the teaching and learning process. For this reason, researchers are interested in seeing the relationship between the madrasah and the teaching style of teachers on learning achievement in Arabic. This study used quantitative methods with a correlation research design and an ex post facto design approach. The sampling technique was stratified random sampling. While the data collection techniques used questionnaires and documentation. Data processing techniques using analysis requirements testing and hypothesis testing. The results showed that  the madrasah  had a significant relationship with Arabic learning achievement at MTs Negeri 1 Pasaman Barat, namely 22.8%, while 77.2% was influenced by other variables. The two teaching styles had  significant relationship with Arabic learning achievement by 12.9%, while 87.1% were influenced by other variables, the three madrasah environments and teacher teaching styles jointly affect Arabic learning outcomes by 21.4% and 78.6% more influenced by other variables. Based on the results of multiple regression analysis, there was a relationship between the madrasah environment and the teaching style of teachers together on Arabic learning achievement where Fcount> Ftable is 4.439> 2.200, then statistically Ha was  accepted and H0 was  rejected.